The Influence of the Number of Workers, Technology, and Investment Realization on Economic Growth on the Island of Java in 2013-2022 - Dwy Desy Rukmana (CV. ULIL ALBAB CORP, 2024)
This paper aims to determine the effect of the number of workers, technology and investment realization on economic growth in Java in 2023-2022. More than half of Indonesia's economy is still concentrated in Java by 57.70 percent. With growth between quarters (qtq) reaching 0.89 percent and between years (yoy) of 4.84 percent. The Java Island economy contributed 2.86 percent growth to national economic growth. Java is still relied on by the government to drive industrial growth in the medium and long term. The Solow growth model assumes that economic growth is influenced by changes in the factors of production of physical capital (savings and investment) and labor (population growth), while technology that describes the level of efficiency is an exogenous variable and is considered as a residual. Labor (TK) has a positive and insignificant effect on economic growth. This means that if TK increases, economic growth will increase. The greater the investment of a country, the greater the level of economic growth that can be achieved. The role of technological innovation in driving economic growth is very important and can have a significant impact. The data collection technique used by the author in this study is to use / utilize secondary data. The data is processed using EViews. The results of this study prove that the number of workers, technology, and investment realization have a positive and significant effect on economic growth.